ANALISIS FINANCIAL STATEMENT FRAUD MENGGUNAKAN PERSPEKTIF TEORI FRAUD DIAMOND (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Bergerak di Sektor Manufaktur Tahun 2016-2019) - Kurnia Purnama Adesya; Totok Dewayanto (Diponegoro Journal of Accounting, 2021)
This study aims to test the influence of diamond fraud elements, namely  pressure, opportunity, rationalization, and capability to the probability of financial statement fraud.This study uses secondary data from the annual report of companies listed on the Indonesia Stock Exchange. Using purposive sampling method, a total of 448 samples were taken from the manufacturing sector which published its annual report in 2016-2019. This study uses logistics regression analysis method to test the element of diamond fraud projected with financial stability, quality of external auditor, composition of independent board of commissioners, change of auditor, and changes of director to the probability of financial statement fraud.The results showed that financial stability has no influence on the probability of financial statement fraud. Then the quality of external auditors has a negative influence on the probability of  financial statement fraud, as well as the composition of the board of commissioners that has a negative influence on the probability of  financial statement fraud. Furthermore, the change of auditors has no influence on the probability of  financial statement fraud and lastly the change of directors has a negative influence on the probability of financial statement fraud.